(untitled) (Community Based Medical Journal, 2024)
The humerus bone of the humans is frequently used in anatomical science, forensic medicine and anthropological studies. This cross-sectional, descriptive study was done on 100 (43 right and 57 left) fully ossified dry human humerus in the Department of Anatomy, Mymensingh Medical College, Bangladesh, between July 2021 to June 2022. A non-random, purposive sampling technique was adopted. The maximum length was determined by measuring the distance between the most superior point on the head of the humerus and the most distal point of the trochlea of the humerus. The length was measured with a metallic scale, while the weight of the humerus was measured using a digital weighing machine. The mean (±SD) maximum length of the right humerus was 304.139 (±17.652) mm, while the left humerus was 300.42 (±20.779) mm. The mean (±SD) weight of the right humerus was 91.069 (±26.944) gm and the left humerus was 93.965 (±32.227) gm. A positive correlation was observed between the maximum length and the weight of the human humerus through regression analysis (r=0.653 and r=0.824 on right and life side respectively). The differences were statistically significant on both sides (P<0.001). CBMJ 2024 January: vol. 13 no. 01 P: 60-65